Bioinspired sensor system for health care and human‐machine interaction - Xue, Jiangtao; Zou, Yang; Deng, Yulin; Li, Zhou (EcoMat (Beijing, China), 2022)
Bioinspired sensor system leads the development of new generation sensor technology with remarkable features like ultra‐sensitivity, low‐power consumption and self‐adaptability. With the help of bioinspired sensor systems, human perception can be quantified and machines can be endowed with specific perception. As an emerging technology, bioinspired sensor system has been widely used in various fields such as industrial, medical, food safety, military and robotic. This review summarizes the recent process of bioinspired sensor system. First, three bionic strategies are defined as bionic materials, bionic structures, and functional bionic according to the sources of bionic inspiration. Second, bioinspired sensor systems with different working mechanisms are summarized and classified into piezoresistive, capacitive, triboelectric, piezoelectric, and other types. Afterward, for applications, the representative works of bioinspired sensor system for health care and human‐machine interaction are focused and introduced, respectively. Finally, the current challenges and prospects of bioinspired sensor system are also discussed. Bioinspired sensor system possesses sensing performance rivaling nature and various bionic functionalities. This review summarizes different bionic strategies and working principles of bionic sensor systems. The representative works of the bioinspired sensor system for health care and human‐machine interaction are focused and introduced, respectively. In addition, the current challenges and prospects of the bioinspired sensor system are also discussed.